The impact of a teacher’s professional identity on his/her occupational happiness: The mediating role of psychological capital - Zhen, Xinheng; Liu, Qian (Nurture, 2023)
Purpose This paper is to explore the factors that influence the professional identity of university teachers on their occupational happiness, and to understand and study the mediating role of psychological capital between a teacher’s professional identity and a teacher’s occupational happiness. Design/Methodology/Approach: This paper uses a quantitative approach to testing. And this paper randomly selected 209 teachers (including full-time teachers and managers) from the Hebei Academy of Fine Arts located in Shijiazhuang, Hebei Province, as the research subjects. Findings: There exists a positive correlation between a teacher's professional identity and their occupational happiness. Additionally, a positive association can be observed between a teacher's professional individuality and their psychological capital. Furthermore, a positive relationship can be identified between a teacher's psychological capital and their professional happiness. Psychological capital plays a mediating role between a teacher’s professional identity and occupational happiness. Conclusion: Professional happiness is a manifestation of happiness at work, and psychological capital and professional happiness have the same theoretical basis and research orientation. The higher their sense of professional identity, the better their attitude towards work, and the higher their sense of professional happiness. Research Limitations/Implications: The sampling only comes from the Hebei Academy of Fine Arts located in Shijiazhuang, Hebei Province, China. The conclusion may not fit all levels of education and teachers' situations. Practical Implications: Universities could focus on improving the teacher's professional identity to improve their occupational Happiness, and universities could train teachers to gain psychological capital to help them keep a positive attitude towards their job to improve their occupational Happiness. Contribution to Literature: This study provides a structural framework for the relationship between psychological capital and occupational happiness that future researchers may use in their studies. The subsequent research could examine this model's applicability to the professional satisfaction of high school teachers or primary school teachers.